Effects of seismic amplification on the stability design of geosynthetic-reinforced soil walls. Issue 5 (October 2022) - Ge, Bin; Ruan, Huaining; Shu, Shuang; Zhang, Fei; Gao, Yufeng
Abstract: Many researches of geosynthetic-reinforced soil (GRS) walls under earthquakes demonstrate seismic acceleration amplification along the wall height. Current design methods of GRS walls often neglect the amplification effect on seismic stability and could yield an unconservative result. A pseudo-static method based on limit equilibrium (LE) analyses is carried out to calculate the distribution of required tension of seismic GRS walls following a top-down procedure. The connection load between the reinforcement and facing is correspondingly determined by the front-end pullout capacity. The approach assumes that the horizontal seismic acceleration coefficient varies linearly from the bottom to the top of GRS walls. The obtained results of the required tension involving the seismic amplification are in good agreement with other LE results in previous studies. Parametric studies are conducted to investigate the effects of horizontal seismic coefficient, primary and secondary reinforcement lengths and wall batter on the seismic stability of GRS walls. The seismic amplification yields more required reinforcement tension, significantly for the lower layers of the GRS wall subjected to strong earthquakes. In this situation, lengthening the bottom 1/2 of reinforcement layers could reduce the required tension to avoid tensile breakage of the reinforcements. Highlights: An approach based on the top-down method which is modified to consider the seismic amplification effect is proposed. Effects of seismic coefficient, reinforcement length and wall batter on the seismic stability of GRS walls are analyzed. Optimization design of GRS walls is discussed.